Decision Making and Knowledge Decision Support Systems: VIII International Conference of RACEF, Barcelona, Spain, November 2013 and International Conference MS 2013, Chania Crete, Greece, November 2013 - Gil-Lafuente, Anna Maria (Springer, 2015)
This book presents recent advancements of research, new methods and techniques, applications and projects in decision making and decision support systems. It explores expert systems and neural networks, knowledge engineering and management, fuzzy sets and systems and computational methods for optimization, data analysis and decision making. It presents applications in Economics, Finance, Management and Engineering. The book undertakes to stimulate scientific exchange, ideas and experiences in the field of decision making in Economy and Management. Researchers and practitioners alike will benefit from this book, when they are dealing with imprecision,